Sequential Photoperiodic Programing of Serotonin Neurons, Signaling and Behaviors During Prenatal and Postnatal Development - Siemann, Justin K.; Green, Noah H.; Reddy, Nikhil; McMahon, Douglas G. (Frontiers in Neuroscience, 2019)
Early life stimuli during critical developmental time frames have been linked to increased risk for neurodevelopmental disorders later in life. The serotonergic system of the brain is implicated in mood disorders and is impacted by the duration of daylight, or photoperiod. Here we sought to investigate sensitive periods of prenatal and postnatal development for photoperiodic programming of DRN serotonin neurons, midbrain serotonin and metabolite levels along with affective behaviors in adolescence (P30) or adulthood (P50). To address these questions we restricted the interval of exposure to prenatal development (E0-P0) for Long summer-like photoperiods (LD 16:8), or Short winter-like photoperiods (LD 8:16) with postnatal development and maturation then occurring under the opposing photoperiod. Prenatal exposure alone to Long photoperiods was sufficient to fully program increased excitability of DRN serotonin neurons into adolescence and adulthood, similar to maintained exposure to Long photoperiods throughout development. Interestingly, Long photoperiod exposure can elevate serotonin and its’ corresponding metabolite levels along with reducing affective behavior, which appear to have both pre and postnatal origins. Thus, exposure to Long photoperiods prenatally programs increased DRN serotonin neuronal excitability, but this step is insufficient to program serotonin signaling and affective behavior. Continuing influence of Long photoperiods during postnatal development then modulates serotonergic content and has protective effects for depressive-like behavior. Photoperiodic programing of serotonin function in mice appears to be a sequential process with programing of neuronal excitability as a first step occurring prenatally, while programing of circuit level serotonin signaling and behavior extends into the postnatal period.